Analisis Nilai-Nilai Pendidikan Islam Dalam Al-Qur'an Surat Luqman Ayat 12-19 - Hamidah, Anida Nur; Bariah, Oyoh; Makbul, M. (Jurnal Ilmiah Wahana Pendidikan, 2025)
This article explores the educational principles of justice in Islam, focusing on the teachings found in Surah Luqman verses 15-19. Justice is not only a fundamental value in Islamic teachings but also a moral and ethical foundation that impacts various aspects of social, economic, political, and legal life. The study aims to examine the significance of justice education in shaping Muslim individuals and communities, emphasizing its practical implementation in daily life. The background discusses the centrality of justice in Islamic doctrine, highlighting its roles in maintaining social balance and fostering harmonious coexistence. The research problem addresses the contemporary relevance of justice education amidst global challenges and technological advancements. The study utilizes a qualitative approach, analyzing interpretations from Islamic scholars and contemporary educational perspectives. Through an analysis of primary sources and scholarly discourse, the research reveals that justice education in Surah Luqman verses 15-19 serves as a moral compass for Muslims, guiding equitable behavior and societal contributions. The findings underscore the importance of integrating justice principles into educational curricula and community practices to nurture ethical responsibility and social cohesion.